A Tale of (almost) 1001 Coefficients: The Deep and Heterogeneous Effects of the EU-Turkey Customs Union - Mario Larch; Aiko F. Schmeißer; Joschka Wanner (JCMS: Journal of Common Market Studies, 2021)
In view of the deferred start of negotiations for the modernization of the customs union between the EU and Turkey (CU-EUT), we looked back and analysed the ex post trade consequences of the CU-EUT. Employing up-to-date econometric best practices for regional integration agreements, we quantified both the total and the heterogeneous trade effects of the CU-EUT. In contrast with most previous studies, our results indicate that the CU-EUT made a significantly positive, large and robust impact, implying there was an additional increase in EU-Turkey trade in manufacturing by 55–65 per cent compared with that during the previously active Ankara Agreement. We also provide evidence that the CU-EUT significantly increased Turkey's trade with non-member countries of the CU-EUT. Additionally, a substantial heterogeneity in the CU-EUT effect was found across different industries as well as for each of its member countries and the direction of trade. We linked the heterogeneity of up to 911 coefficient estimates to the differences in initial trade costs and show that it cannot be ascribed to reductions in bilateral tariff rates.
Keywords: 330; gravity model; European integration; country-specific effects